Customer-friendly Approach or Pidginization of German Tourist Discourse (Altre Modernità, 2012)
If the sentences or phrases like Fast Food-Konzept in Chile, Leonardo goes Gastronomie, Der Claim „Inspiration for modern living“, WM-Countdown läuft; Deutschland ist die fünftgrößte Incoming-Destination weltweit und … are considered, the first impression is that this is a typical mixture of both English and German. To all intents and purposes, they support the main part of a definition of pidgin language. Communication plays a central role in tourism. As emphasized by numerous authors, it is a personification of tourism; conversely tourism could be said to totally encompass a system of communication. As it is a crucial component of the industry, tourist discourse not only serves as a medium for buying/selling tourist products, it also assumes the role of the product itself within the complexity of various economic, technological and political processes in tourism. If analyzed within linguistic norms, discussion of Anglo-American influence on the German tourist discourse should focus on the problem of erosion of the national language, due to the impact of these Ango-Americanisms. The German tourist discourse aims at a customer-friendly approach in order to attract potential buyers or guests, all of which results in a slightly pidginized version of the German tourist discourse.